Policies for low-carbon and affordable home heating: A French outlook. (April 2021) - Giraudet, Louis-Gaëtan; Bourgeois, Cyril; Quirion, Philippe
Abstract : Energy demand for residential heating is targeted in France by a number of subsidy programmes (tax credits, zero-interest loans, reduced VAT, white certificates) and the carbon tax. We assess the cost-effectiveness and distributional impacts of these policies using Res-IRF, an energy-economy model that integrates relevant economic, behavioural and technological processes. We find that, without further specification of revenue recycling, the carbon tax is the most effective, yet most regressive, policy. Subsidy programmes save energy at a cost of €0.05–0.08 per lifetime discounted kilowatt-hour, or €300–800/tCO2-eq; one euro of public money spent on subsidy programmes induces €1.0–1.4 private investment in home energy retrofits. Targeting subsidies towards low-income households, who tend to live in energy inefficient dwellings, increases leverage, thus reconciling economic efficiency and equity. The public cost of subsidies – €3 billion in 2013 – is outweighed by carbon tax proceeds from 2025 onwards, were the tax rate to grow as initially planned by the government. Meeting the long-term energy saving targets set by the government however requires adjusting subsidy programmes to better address rental housing. Lastly, an order-of-magnitude discrepancy between simulated and observed numbers of zero-interest loans points to economic and psychological barriers that require further investigation. Highlights: Economic, environmental and distributional impact of French residential policies. Focus on tax credits, zero-interest loans, white certificates and the carbon tax. Carbon tax most effective, yet most regressive when recycling left unspecified. Leverage higher when subsidies are targeted towards low-income households. Hardly any policy effectively tackles the stock of rental housing.